The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fmicb.2020.00902
|View full text |Cite
|
Sign up to set email alerts
|

Improving HIV Outgrowth by Optimizing Cell-Culture Conditions and Supplementing With all-trans Retinoic Acid

Abstract: The persistence of replication-competent HIV reservoirs in people living with HIV (PLWH) receiving antiretroviral therapy (ART) is a barrier to cure. Therefore, their accurate quantification is essential for evaluating the efficacy of new therapeutic interventions and orienting the decision to interrupt ART. Quantitative viral outgrowth assays (QVOAs) represent the "gold standard" for measuring the size of replication-competent HIV reservoirs. However, they require large numbers of cells and are technically ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 92 publications
3
18
0
Order By: Relevance
“…Our observation that RA is capable of reactivating replication-competent latent SIV is similar to the findings of Li et al, who showed that acitretin, an FDA-approved homologue of RA also leads to increased transcription of activated HIV-1 provirus [47]. Likewise, Zhang et al showed that supplementation of RA during QVOA improves the reactivation of the latent reservoir in sorted human memory CD4 + T cells [21].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our observation that RA is capable of reactivating replication-competent latent SIV is similar to the findings of Li et al, who showed that acitretin, an FDA-approved homologue of RA also leads to increased transcription of activated HIV-1 provirus [47]. Likewise, Zhang et al showed that supplementation of RA during QVOA improves the reactivation of the latent reservoir in sorted human memory CD4 + T cells [21].…”
Section: Discussionsupporting
confidence: 90%
“…Recently, Zhang et al, 2020, showed that QVOA estimates could be improved by refining cell culture conditions after T cell receptor (TCR) stimulation of sorted memory CD4 + T cells and later supplementation with retinoic acid (RA) for improved viral outgrowth [ 21 ]. However, it remains to be determined whether the supplementation with RA could be modified to improve QVOA estimates in latently-infected cells obtained in vivo from non-human primate (NHP) models such as rhesus macaques (RMs).…”
Section: Introductionmentioning
confidence: 99%
“…Nested real-time PCR quantifications [43]), showed a minor but statistically significant increase in HIV-DNA integration between week 12 and Week 24; this may be explained by the recirculation of the T cells from tissues, consistent with the metformin-mediated decrease in the frequency of colon-infiltrating CD4 + T-cells and in the plasma levels of CCL20, a chemokine involved in CCR6 + T cell trafficking [74]. In contrast, changes in the frequency of cells carrying inducible MS HIV-RNA (measured by TILDA [66]), and replication-competent HIV reservoirs (measured by QVOA [75]) did not reach statistical significance between Baseline, Week 12, and Week 24, consistent with the low expression of phosphorylated mTOR in blood cells. These results are in line with the well-described stability of HIV reservoirs under ART and the difficulty to perturb HIV latency upon short time interventions [2À4].…”
Section: Discussionmentioning
confidence: 56%
“…A simplified VOA was performed, as we previously described (50). Briefly, memory CD4+ T-cells were cultured at 1×10 6 cells/well in 1 ml of media (RPMI, 10% FBS, 1% Penicillin/Streptomycin) in a 48-well plate (Costar) coated with CD3 Abs (1 μg/ml; BD Biosciences, Clone UCHT1) and in the presence of soluble CD28 Abs (1 μg/ml; BD Biosciences, Clone CD28.2).…”
Section: Methodsmentioning
confidence: 99%